(untitled) (Communications in Computational Physics, 2020)
A surface based lattice Boltzmann impedance boundary condition (BC) using Ozyoruk's model [J. Comput. Phys., 146 (1998), pp. 29-57] is proposed and implemented in PowerFLOW. In Ozyoruk's model, pressure fluctuation is directly linked to normal velocity on an impedance surface. In the present study, the relation between pressure and normal velocity is realized precisely by imposing a mass flux on the surface. This impedance BC is generalized and can handle complex geometry. Combined with the turbulence model in the lattice Boltzmann solver PowerFLOW, this BC can be used to model the effect of a liner in presence of a complex 3D turbulent flow. Preliminary simulations of the NASA Langley grazing flow tube and Kundt tube show satisfying agreement with experimental results.